“Life is about trying to find a better place to live”: Discourses of dwelling in a pro-recovery suicide forum - Mike Alvarez (Qualitative Research in Medicine & Healthcare, 2022)
In the two decades since the advent of Web 2.0, scholars of cybersuicide have identified many beneficial and harmful uses of the internet. However, the discursive meanings interactionally created by suicide website users have scarcely been attended to. The present study uses the theory and method of cultural discourse analysis (CuDA) to arrive at meanings about place that radiate from online communication among users of SuicideForum.com (SF), a pro-recovery website. Analyses of 2,119 posts across 131 threads reveal two overarching discursive themes. The first speaks to problematic discourses about place, including the role of placelessness and entrapment in the genesis of suicidality and its affective states, leading to further diminution of experiential worlds. The second theme taps into participants’ notions of what constitutes safe spaces, such as the presence of empathetic others who respect one’s timetable for personal disclosure, and the freedom to experiment with new ways of inhabiting the world. The study has numerous implications for clinical practice, including recasting psychological disturbances in terms of self-world relations and reconsidering involuntary psychiatric hospitalization in light of forum participants’ preoccupation with entrapment.